Optimalisasi Manajemen Konflik: Perilaku Asertif Dalam Keperawatan - Cicilia Ika Wulandari; Enie Novieastari; Sri Purwaningsih (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
Professional nursing is needed to provide quality services with assertive behavior. Assertivebehavior for nurses is important because nurses work always interacting with others. The purposeof this study was to describe a description of assertive behavior in hospital nursing. Researchrenewal can be used to optimize conflict management, assertive behavior in nursing. The methodused in this study is descriptive research with survey methods. Implementation of research startsfrom situation analysis, problem identification, determining priority problems, making actionplans, implementation, and evaluation. The study sample involved 55 nurses who were randomlyselected in the inpatient room. Sample calculation uses the Rule of Thumb formula and obtained55 nurses. The identification results showed that there were nurses who were not assertive, namely53% of passive nurses and 25% of nurses being aggressive. Non-assertive behavior in work cancause conflicts, such as task conflicts, communication conflicts, structural conflicts, intrapersonalconflicts, and conflicts between groups. Conflict management abilities, especially assertivetechniques aim to limit and avoid violence, by encouraging positive behavioral changes for theparties involved, especially assertive behavior. Conflicts that can be managed properly can havethe effect of quality nursing services. The recommendations provided are able to strengthenregulations and increase conflict management knowledge, especially assertive behavior innursing.